PENGETAHUAN IBU HAMIL TENTANG TABLET TAMBAH DARAH DI UPTD PUSKESMAS BABELAN 1 - Honey Iskandar; Umul Angga Brahmono; Nida’ Ulayya Maghfiroh (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
Basic Health Research Data (Riskesdas) states that in 2018 48.9% of pregnant women experienced anemia. This figure increased from 2013 where 37.1% of pregnant women were anemic. Iron is one of the important minerals needed by humans. This mineral can also serve as a component to form myoglobin (a protein that carries oxygen to muscles). Pregnant women need iron more than double their pre-pregnancy needs. This happens because during pregnancy, blood volume increases by up to 50% so it requires more iron to form hemoglobin. Blood volume increases due to blood thinning, the need for placental formation and fetal growth. Causes and risk factors for pregnant women who experience anemia include lack of balanced nutrition for mother and fetus, too close pregnancy distance, pregnant women experiencing chronic energy deficiency (KEK), lack of intake of foods containing iron. In the preliminary survey, researchers obtained data that 70 of 124 pregnant women in the last three months in 2021 had anemia with Hb blood levels<11% based on laboratory results at the UPTD of the Babelan I Health Center. The impact of anemia on pregnant women is increasing morbidity including bleeding. , premature rupture of membranes, the risk of low birth weight babies (LBW). This study aims to describe the knowledge of pregnant women about blood-added tablets at the UPTD Puskesmas Babelan I. The method in this research is descriptive quantitative. The sampling technique in this study was using purposive sampling with a sample of 173 people in June 2022. The results showed that the knowledge of pregnant women about blood-added tablets at the UPTD Puskesmas Babelan I in the category of good knowledge level was 147 people (85.0%), sufficient knowledge as many as 20 people (11.5%) and lack of knowledge as many as 6 people (3.5%). The conclusion of this research is that the highest level of knowledge is 147 people with good category